TREATMENT OF RESPIRATORY DISEASE IN PIGS IN EFFORTS TO INCREASE LIVESTOCK PRODUCTIVITY IN PENARUKAN VILLAGE, KERAMBITAN, TABANAN - Suarjana, I Gusti Ketut; Besung, I Nengah Kerta; Rompis, Aida Lousie Tenden; Gelgel, Ketut Tono Pasek (Buletin Veteriner Udayana, 2020)
Community service has been conducted on the treatment of respiratory diseases in pigs in an effort to increase livestock productivity in Desa Penarukan, Kerambitan, Tabanan. This dedication aims to provide knowledge to the community about how to manage pigs intensively, the prevention and eradication of diseases of pigs effectively and efficiently so that the maximum production of the livestock. Methods of service include house-to-house acts, especially to sickly breeders, initiating treatment with antibiotics, worm medicines, vitamins and minerals and providing counseling on how to prevent respiratory respiratory complex desease (PRDC) disease in pigs known as porcine respiratory complex desease (PRDC). The result obtained as follows: the community is  give a positive response to activities and teams held home-to-home services to tens of breeders pigs whose  reportedly suffered from PRDC spread over five  banjar adat in Penarukan village. The sick pigs generally ranged from 1 to 3 months and treated as many as 20. Furthermore, based on the monitoring of the team and the report of breeders on the seventh day after being given treatment of the pigs showed no clinical symptoms and was declared cured.